ANALISIS PENGARUH DIMENSI SERVQUAL TERHADAP PEMILIHAN JASA TRANSPORTASI UDARA (MASKAPAI PENERBANGAN) RUTE JAKARTA – SURABAYA - Shorin Hendarin Prakoso; Armanu - Thoyib; Surachman - - (Sekolah Pascasarjana Universitas Brawijaya, 2010)
ABSTRACT The increase in number of airlines industry in Indonesia has caused price competition between airlines company, especially for the Jakarta – Surabaya route. In order to survive in this industry, the airlines company has made efficiency to reduce the costs. So that, as the result service quality became lower, and it will affecting consumer satisfaction. The objectives of this research are to analyze the effect of service quality dimension (SERVQUAL), which consist of tangible, reliability, responsiveness, assurance, and empathy, towards consumer concern in choosing air transportation service (airlines industry), for Jakarta – Surabaya route, and to analyze which of those five variables has the dominant effect to the consumer for selecting air transportation service, for Jakarta – Surabaya route. This research took place in Jakarta International Airport, Soekarno – Hatta by using the purposive sampling method, with involving 150 respondents as sample. The F – test and t – test with α 5 % was used to examined the significance level of variables. The hypothesis was examined by using multiple regression analysis. The result of this research shows that service quality (SERVQUAL) dimension, which consist of tangible, reliability, responsiveness, and assurance has affecting consumer concern partially in choosing air transportation service, for Jakarta – Surabaya route, whereas the empathy doesn’t affecting consumer concern in choosing air transportation service. Among those five variables, the reliability is the dominant factor that affecting consumer concern in choosing air transportation service, for the Jakarta – Surabaya route.